Spatial Distribution of Whitefly Species (Hemiptera: Aleyrodidae) and Identification of Secondary Bacterial Endosymbionts in Tomato Fields in Costa Rica - Can Vargas, Xareni (2020)
In Costa Rica, tomato (Solanum lycopersicum Linnaeus) Linnaeus (Solanales: Solanaceae) is one of the crops most severely affected by the whiteflies (Hemiptera: Aleyrodidae) Trialeurodes vaporariorum (Westwood) and the Bemisia tabaci (Gennadius) species complex. The objective of this study was to monitor the spatial distribution and diversity of these species and to detect the presence of secondary bacterial endosymbionts in individuals collected in areas of intensive tomato production. In total, 628 whitefly individuals were identified to the species level using restriction analysis (PCR-RFLP) of a fragment of the mitochondrial cytochrome C oxidase I gene (mtCOI). Trialeurodes vaporariorum was the predominant species, followed by B. tabaci Mediterranean (MED). Bemisia tabaci New World (NW) and B. tabaci Middle East-Asia Minor 1 (MEAM1) were present in lower numbers. The mtCOI fragment was sequenced for 89 individuals and a single haplotype was found for each whitefly species. Using molecular markers, the 628 individuals were analyzed for the presence of four endosymbionts. Arsenophonus Gherna et al. (Enterobacterales: Morganellaceae) was most frequently associated with T. vaporariorum, whereas Wolbachia Hertig (Rickettsiales: Anaplasmataceae) and Rickettsia da Rocha-Lima (Rickettsiales: Rickettsiaceae) were associated with B. tabaci MED. This study confirmed that B. tabaci NW has not been completely displaced by the invasive species B. tabaci MED and B. tabaci MEAM1 present in the country. An association was found between whitefly species present in tomato and certain secondary endosymbionts, elevation was the most likely environmental factor to affect their frequency.